Species of white-tailed forest rats hunted and traded, their conservation status and habitat characteristics, in North Sulawesi, Indonesia - Sylvia Laatung; Asnath Maria Fuah; Burhanuddin Masy'ud; Cece Sumantri; Salundik Dohong (Society for Indonesian Biodiversity, 2021)
Abstract. Laatung S, Fuah AM, Masy’ud B, Sumantri C, Salundik. 2021. Species of white-tailed forest rats hunted and traded, their conservation status and habitat characteristics, in North Sulawesi, Indonesia. Biodiversitas 22: 2778-2784. The tradition of hunting and trading white-tailed forest rats, especially in North Sulawesi, has been practiced for generations. This poses a threat to the existence of these animals in their natural habitat leading to the extinction of some hunted species. In the past, studies on white-tailed rats being hunted and traded on Sulawesi is still lacking. Therefore, the purpose of this study is to identify the species of white-tailed forest rats hunted and traded, their conservation status and habitat characteristics in North Sulawesi. This study was conducted in April to June 2018 in Minahasa and Bolaang Mongondow District, North Sulawesi. The survey methods used involved visiting hunters, recording and taking pictures of the species of rats being hunted and traded. All samples of white-tailed rats were identified in the Zoological Laboratory, Indonesian Institute of Sciences Cibinong Bogor, West Java. Furthermore, ascertaining the general characteristics of the habitat was carried out using a general survey in locations known as distribution areas in North Sulawesi. The identification of 125 individuals consists of 8 species of white-tailed forest rats from 7 genera, which are commonly hunted. They include Rattus xanthurus (Gray, 1867), Bunomy fratrorum (Thomas, 1896), Lenomys meyeri (Jentink, 1879), Paruromys dominator (Thomas, 1921), Echiotrix leucura (Gray, 1879), Taeromys taerae (Sody, 1932), Maxomys hellwaldi (Jentink, 1879) and Maxomys musschenbrooki (Jentink, 1878). Four out of the eight species of white-tailed forest rats are protected species according to the IUCN Redlist. The white-tailed forest rats identified in this study, were caught in secondary forest and plantation, ranging from an altitude of 500 - 1.500 meters above sea level. Their main sources of feed include Areca catechu, Piper aduncum, Ficus spp., and Arenga piñnata.